Pengaruh Etika Kerja Terhadap Kinerja Adaptif Melalui Kepemimpinan Transformasional Pada Dinas Perhubungan Kabupaten Seram Bagian Barat - Sangadji, Bharatayuda Junipratomo; Bahasoan, Aminah; Selanno, Hendry (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the effect of work ethics on employees' adaptive performance at the Department of Transportation of West Seram Regency, with transformational leadership as a mediating variable. The research uses a quantitative approach with the Partial Least Square Structural Equation Modeling (PLS-SEM) analysis technique. A total of 126 employees were selected using purposive sampling. The instrument used was a five-point Likert scale questionnaire that had passed validity and reliability tests. The results showed that work ethics had a positive and significant effect on adaptive performance. Work ethics also had a positive and significant effect on transformational leadership. Moreover, transformational leadership had a positive and significant effect on adaptive performance. Another important finding is that transformational leadership significantly mediates the influence of work ethics on adaptive performance. This indicates that strong work ethics not only directly affect employees' adaptability but also through the crucial role of transformational leadership within the organization. Therefore, strengthening work ethics should be a key focus in efforts to improve adaptive performance, particularly by fostering transformational leadership styles.